Impact of timing of urinary catheter removal on voiding dysfunction after radical hysterectomy for early cervical cancer. Issue 8 (8th July 2022) - Huepenbecker, Sarah; Santía, María Clara; Harrison, Ross; Dos Reis, Ricardo; Pareja, Rene; Iniesta, Maria D; Meyer, Larissa A; Frumovitz, Michael; Zorrilla-Vaca, Andres; Ramirez, Pedro T
Abstract : Objectives: To evaluate whether the timing of postoperative urinary catheter removal is associated with voiding dysfunction after radical hysterectomy for early cervical cancer within contemporary surgical practice. Methods: We performed an institutional retrospective cohort study of patients who underwent Piver type II-III open or minimally invasive radical hysterectomy for early-stage cervical cancer (International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IA1 with lymphovascular invasion to stage IIA) between January 2006 and December 2019. We compared voiding dysfunction (inability to spontaneously void with a post-void residual <100 mL after catheter removal) and outcomes based on postoperative timing of urinary catheter removal using univariate and multivariate logistic regressions. Results: Among 234 patients, 86 (36.8%) underwent open surgery and 112 (47.9%) used enhanced recovery after surgery (ERAS) pathways. 29 (12.4%) patients had urinary catheter removal between 1–5 days postoperatively (group 1), 141 (60.3%) between 6–10 days (group 2), and 64 (27.3%) between 11–15 days (group 3). The overall rate of voiding dysfunction was 11.5%, with no difference between group 1 (17.2%), group 2 (11.3%), and group 3 (9.4%) (p=0.54). Group 1 had a significantly shorter time from surgery to spontaneous voiding (4 days, IQR 3–5 days) compared with group 2 (8 days, IQR 7–10 days) and group 3 (13 days, IQR 11–15 days) (p<0.01). There was no difference in hospital length of stay, urinary tract infection, or re-admission due to a genitourinary complication within 60 days of surgery based on timing of catheter removal. On multivariate analysis, the odds of voiding dysfunction did not differ by tumor size, type of hysterectomy, cancer stage, surgical approach, ERAS timeframe, or timing of catheter removal group. Conclusion: There was no difference in voiding dysfunction or postoperative genitourinary complications based on timing of urinary catheter removal after radical hysterectomy. Early catheter removal should be considered in this population.